A decision support process for the selection of sustainable public ICT project investments - Muhammed Rasit Ozdas; Ozel Sebetci; Tamer Eren; Hadi Gokcen (International Journal of Information Systems and Project Management, 2025)
The allocation of limited public resources to public investments necessitates selecting projects with the highest social and economic value, along with the greatest likelihood of success. However, the literature lacks well-defined criteria to measure the alignment of such projects with national policies, social benefits, and institutional capabilities. This paper aims to fill this gap by presenting a process methodology and a set of criteria for evaluating and prioritizing public sector ICT projects. A project selection process is defined with a comprehensive criteria set, and it was tested on 11 carefully selected information and communication technology projects. A process has been defined consisting of prerequisite elimination, criteria weighting, project scoring, and verification. Both AHP and TOPSIS methods were utilized. The study also attempts to measure social benefits with respect to Türkiye’s national priorities, through more tangible sub-criteria. To the best of our available knowledge, the study provides the most comprehensive set of criteria for selecting ICT investment projects in the public sector. The findings reveal that projects aligned with national priorities and providing high social benefits were ranked highest. The fact that project criteria provide feedback from a broad perspective shows that information systems can also support project maturation, along with project selection.